Anti-cracking admixture for mass concrete and application of anti-cracking admixture

By using crack-resistant admixtures of modified graphene oxide and alkali-excited steel slag micro powder in large volume concrete, the problem of stable dispersion of graphene oxide in cement-based materials is solved, and the crack-resistant and permeability of concrete is significantly improved.

CN119683891AActive Publication Date: 2025-03-25THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510203407.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of stable dispersion of graphene oxide in concrete, which leads to its inability to fully exert the effects of reinforcement, toughening and crack resistance in cement-based materials.

Method used

By adding modified graphene oxide and alkali-activated steel slag powder to the concrete, a crack-resistant blend is formed to improve the crack-resistant properties of large-volume concrete. Modified graphene oxide is modified by linear polyether or branch polyether to increase its surface functional groups and improve its interaction with the cement matrix.

Benefits of technology

It achieves excellent overall crack resistance and seepage resistance of large-volume concrete, reduces the invasion and expansion of cracks, and enhances the density and durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683891A_ABST
    Figure CN119683891A_ABST
Patent Text Reader

Abstract

The invention provides an anti-cracking admixture for mass concrete, which is prepared from the following components in parts by mass: 50 to 80 parts of steel slag micro powder, 20 to 30 parts of carbide slag, 25 to 30 parts of anti-cracking agent and 0.5 to 1 part of modified graphene oxide, the invention also provides mass concrete which comprises the following components in proportion: 320-340 kg / m < 3 > of cement, 90-100 kg / m < 3 > of mineral powder, 50-80 kg / m < 3 > of fly ash, 800-850 kg / m < 3 > of sand, 780-820 kg / m < 3 > of gravel, 95.5-141 kg / m < 3 > of anti-crack admixture, 5-8 kg / m < 3 > of water reducer and 150-180 kg / m < 3 > of water. The modified graphene oxide with good dispersibility and the alkali-activated steel slag micropowder are added into the concrete, so that the crack resistance of the mass concrete is improved; due to the two-dimensional nanostructure of the modified graphene oxide, the modified graphene oxide has an extremely huge specific surface area, and interface bonding and microscopic filling with a cement matrix are facilitated; the active steel slag micro powder can further form a more compact microstructure network.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to an anti-cracking admixture for mass concrete and application thereof. Background Art

[0002] Structural durability failure caused by deterioration mechanisms such as carbonation corrosion, chloride ion penetration, and alkali-aggregate reaction often occurs in concrete buildings. A large number of studies have found that durability problems are mainly caused by concrete cracks. Once concrete cracks appear, the interior of the concrete is in direct contact with the air, and harmful impurities in the air enter the concrete. The steel bars inside the concrete will be corroded by the harmful impurities, causing the concrete and steel bars to loosen, thereby causing the concrete wrapped around the steel bars to fall off seriously.

[0003] The most fundamental reason for concrete cracking is that the various properties of the raw materials are uneven and the combination of the raw materials causes the concrete to shrink and deform. The shrinkage of concrete generally includes five types: plastic shrinkage, autogenous shrinkage, drying shrinkage, temperature shrinkage and carbonization shrinkage. Adjusting the curing method, adding mineral admixtures and additives can reduce the problem of concrete cracking to a certain extent. The two-dimensional nanostructure of graphene oxide (GO) gives it an extremely large specific surface area, which is conducive to the interface bonding and micro-filling with the cement matrix. The functional groups carboxyl and hydroxyl on the surface help to improve the interaction with the cement matrix, promote interfacial bonding, and reduce crack initiation and expansion. To give full play to the excellent effect of GO on cement-based materials, GO must be uniformly dispersed in the cement-based material in a single layer or a few layers. However, the stable dispersion of GO in the cement hydration medium is still the key to exerting the effects of GO on cement-based materials such as strengthening, toughening and crack resistance. If this problem can be solved, large-volume concrete with excellent performance can be obtained. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an anti-cracking admixture for mass concrete, which improves the anti-cracking performance of mass concrete by adding modified graphene oxide and alkali-activated steel slag powder with good dispersibility into concrete.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides an anti-cracking admixture for mass concrete, wherein the anti-cracking admixture comprises, by weight, 50-80 parts of steel slag powder, 20-30 parts of carbide slag, 25-30 parts of anti-cracking agent, and 0.5-1 part of modified graphene oxide; the modified graphene oxide is at least one of linear polyether modified graphene oxide and dendritic polyether modified graphene oxide; the steel slag powder and carbide slag need to be ground, screened, mixed evenly, and calcined at 600-800°C for 1-2 h before use.

[0006] The linear polyether-modified graphene oxide is obtained by anionic ring-opening polymerization of deprotonated graphene oxide as an initiator and an epoxy compound; The preparation method of the dendritic polyether modified graphene oxide is: (1) The modified silane coupling agent is used to couple the hydroxyl groups on the surface of graphene oxide, and the protective groups are hydrolyzed to obtain amino-modified graphene oxide; (2) Aminated amino groups and epoxy groups in graphene oxide are ring-opened under alkaline conditions to obtain polyhydroxy-modified graphene oxide; (3) Deprotonating the polyhydroxy-modified graphene oxide and using it as an initiator to undergo anionic ring-opening polymerization with an epoxy compound to obtain dendritic polyether-modified graphene oxide; The modified silane coupling agent has the following molecular structure: , wherein R is at least one of a methyl group and an ethyl group.

[0007] It should be noted that replacing part of the fly ash with steel slag can prolong the hydration time, reduce the heat of concrete hydration, and reduce the stress of the internal structure of concrete caused by shrinkage, thereby enhancing the crack resistance of concrete. However, the internal composition of steel slag contains an indefinite amount of free calcium oxide and free magnesium oxide. The free calcium oxide and free magnesium oxide are very unstable at room temperature, and are prone to cracking and expansion during the use of steel slag. As the specific surface area of ​​the ground steel slag powder increases, the contact area between the steel slag powder and the mixing water increases, which accelerates the hydration rate of the steel slag and effectively improves the activity of the steel slag; the synergy of alkali excitation and thermal excitation can accelerate the depolymerization of the steel slag and further improve the activity of the steel slag, forming a denser microstructure network.

[0008] Preferably, the steel slag powder and carbide slag are ground and then screened through a 300-400 mesh sieve.

[0009] Preferably, the preparation method of the linear polyether modified graphene oxide is as follows: 1 part of graphene oxide and 50-60 parts of methanol solution were ultrasonically treated for 20-30 min and then added to a reactor. 5-6 parts of sodium methoxide solution were added under nitrogen conditions and stirred at 60-70 °C for 3-4 h. The obtained solution was filtered and the filter cake was washed with methanol and toluene in turn, and dried to obtain deprotonated graphene oxide. It was added to a high-pressure reactor and 8-10 parts of epoxy compound were added under nitrogen conditions. The reaction was carried out at 80-100 °C for 1-3 h. After the reaction, distilled water was added to terminate the reaction. After filtering, the filter cake was washed with ethanol and water in turn and dried to obtain linear polyether modified graphene oxide.

[0010] Preferably, the preparation method of the dendritic polyether modified graphene oxide is as follows: S1. Add 1 part of 1,7-bis-BOC-1,4,7-triazaheptane and 20-30 parts of anhydrous dimethyl sulfoxide solution to a reaction kettle. Under a nitrogen atmosphere, add potassium iodide and heat to 100-110 °C. Then slowly add 1.05-1.1 parts of 3-chloropropyltriethoxysilane. After reacting for 10-12 hours, cool to room temperature, remove the solvent by rotary evaporation, wash with anhydrous ether, and vacuum dry to obtain a modified silane coupling agent. S2. Ultrasonic dispersion of 1 part of graphene oxide in 100-120 parts of anhydrous ethanol for 30-40 min, then adjusting the pH to 3-4 with 3-4 mol / L hydrochloric acid solution, transferring it into a reactor, dispersing 2-3 parts of the modified silane coupling agent obtained in step S1 in 10-20 parts of anhydrous ethanol and adding dropwise thereto in a water bath at 60-70 °C, reacting for 5-6 h, adding 30-40 parts of trifluoroacetic acid and continuing stirring for 30-40 min, filtering the obtained solution after the reaction, washing the filter cake with anhydrous ethanol and deionized water in turn, and drying to obtain amino-modified graphene oxide; S3. Add 1 part of amino-modified graphene oxide and 70-80 parts of dry tetrahydrofuran into a beaker and ultrasonicate for 30-40 minutes. Transfer it to a reactor under a nitrogen atmosphere at a temperature of 0-10 °C, add 2-3 parts of propylene oxide, heat to room temperature for reaction for 1-2 hours, then heat to 50-60 °C for reaction for 10-16 hours. After the reaction, filter the obtained solution, wash the filter cake with anhydrous ethanol, and dry to obtain polyhydroxy-modified graphene oxide. S4. After ultrasonic treatment for 20-30 min, add 1 part of the polyhydroxy-modified graphene oxide obtained in step S3 and 50-60 parts of methanol solution into a reactor, add 5-6 parts of sodium methoxide solution under nitrogen, and stir at 60-70°C for 3-4 h. Filter the obtained solution, wash the filter cake with methanol and toluene in turn, and dry to obtain deprotonated polyhydroxy-modified graphene oxide; add it into a high-pressure reactor, add 20-25 parts of epoxy compound under nitrogen, and react at 80-100°C for 1-3 h. After the reaction, add distilled water to terminate the reaction. After filtering, wash the filter cake with ethanol and water in turn and dry to obtain branch polyether modified graphene oxide.

[0011] More preferably, the epoxy compound is one or more of ethylene oxide, propylene oxide and glycidol.

[0012] In a second aspect, the present invention provides a mass concrete comprising, in terms of mix ratio, 320-340 kg / m 3 、Mineral powder 90~100 kg / m 3 、Fly ash 50~80 kg / m3 , sand 800~850 kg / m 3 , Crushed stone 780~820 kg / m 3 , Anti-cracking admixture 95.5~141 kg / m 3 , water reducing agent 5~8 kg / m 3 , Water 150~180 kg / m 3 ; The anti-cracking admixture is the anti-cracking admixture prepared by the above method.

[0013] Preferably, a method for preparing mass concrete comprises the following steps: 1) Disperse the anti-cracking admixture in water, ultrasonicate for 5-10 minutes, mix cement, mineral powder, fly ash, sand and gravel according to the mix ratio, stir for 2-3 minutes, add water and the dispersed anti-cracking admixture, stir for 2-3 minutes, then add the water reducer, continue stirring for 8-16 minutes, and discharge; 2) Casting, standard curing, demoulding, and obtaining large volume concrete.

[0014] The graphene oxide used in the present invention can be sourced from commercial products or can be homemade, and its preparation raw materials and preparation methods are all conventional techniques.

[0015] Beneficial Effects

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1) Adding the anti-cracking admixture prepared by the present invention can give large-volume concrete excellent overall anti-cracking and anti-permeability properties; the two-dimensional nanostructure of modified graphene oxide gives it an extremely large specific surface area, which is conducive to interfacial bonding and micro-filling with the cement matrix, and the functional group carboxyl on the surface helps to improve the interaction with the cement matrix, promote interfacial bonding, and reduce crack initiation and expansion.

[0017] 2) The modified graphene oxide in the anti-cracking admixture of the present invention is preferably a dendritic polyether modified graphene oxide. The graphene oxide is modified so that the number of modifiable groups on its surface is increased. The polyether groups are introduced on the surface of the graphene oxide through anionic ring-opening polymerization, thereby playing a dispersing role.

[0018] 3) Under high temperature, carbide slag decomposes into calcium oxide as an alkali metal activator. The synergistic effect of alkali excitation and thermal excitation can accelerate the activity of steel slag powder, forming a denser microstructure network and further improving the anti-cracking performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The preparation routes of the modified graphene oxide of the present invention, wherein route 1 is the preparation route of linear polyether modified graphene oxide, and route 2 is the preparation route of dendritic polyether modified graphene oxide; Figure 2 The NMR spectrum of the modified silane coupling agent synthesized by the present invention; Figure 3 The X-ray diffraction patterns of the linear polyether-modified graphene oxide and the branch polyether-modified graphene oxide 1 of the present invention are shown. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0022] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0023] The raw materials and equipment used in the embodiments and comparative examples are described as follows: Cement: Portland cement, PII 52.5R, China Resources Cement; Fly ash: Wuhan Lianhekang Biotechnology Co., Ltd.; Sand: river sand, medium sand (3.0-2.3), Macheng Chuhe Sand and Gravel State-owned Operation Co., Ltd.; Steel slag: converter steel slag (SS) produced by Handan Iron and Steel Company of Hebei Iron and Steel Group; Calcium carbide slag: Chixiang Building Materials, Kangshan Street, Huzhou; Mineral powder: S95 grade, Yangxin Fuda Mineral Powder Grinding Co., Ltd. Crushed stone: Xinxin Mining Co., Ltd., Xianning City, Xianning District, particle size is 5~10 mm; Anti-cracking agent: HME-V concrete anti-cracking agent, purchased from Jiangsu Subot; Water reducing agent: polycarboxylic acid high-efficiency water reducing agent (40%), purchased from Xi'an Shawshank Building Materials Co., Ltd.; Graphite: natural flake graphite, 325 mesh, Sinopharm Chemical Reagent Co., Ltd.; Potassium permanganate: purchased from Shanghai Shanpu Chemical Co., Ltd.; Concentrated sulfuric acid: purchased from Sinopharm Chemical Reagent Co., Ltd.; Sodium nitrate: purchased from Shanghai Shanpu Chemical Co., Ltd.; Hydrogen peroxide: purchased from Sinopharm Chemical Reagent Co., Ltd. Sodium methoxide: Product No. S51720, purchased from Shanghai Jizhi Biochemical Technology; Propylene oxide: product number P-91745, purchased from Tianjin Xiensi Biochemical Technology; 1,7-Bis-BOC-1,4,7-triazaheptane: product number 1065505, purchased from Shanghai Haohong Biopharmaceutical Technology; Potassium iodide: product number P-89681, purchased from Tianjin Xiensi Biochemical Technology; 3-Chloropropyltriethoxysilane: product number C-00422, purchased from Tianjin Xiensi Biochemical Technology; Graphene oxide (self-made): Under ice bath conditions, add 80 mL of concentrated sulfuric acid and 3 g of sodium nitrate to the reactor, add 1.5 g of graphite and 10 g of potassium permanganate mixture in batches over 1.5 h, keep the reaction temperature at -5~5 °C, stir for 2 h; raise the temperature to 30 °C, react for 3 h, then add 150 mL of deionized water within 30 min; raise the temperature to 80 °C, react for 30 min, slowly add 150 mL of deionized water and 18 mL of hydrogen peroxide, the solution turns golden yellow and the reaction is over, filter the filter cake, and wash it three times with deionized water by centrifugation to obtain graphene oxide.

[0024] Linear polyether modified graphene oxide 1 part of graphene oxide was added into a reactor, and 6 parts of sodium methoxide solution and 60 parts of methanol solution were added under nitrogen conditions, and stirred at 70°C for 3 h. The obtained solution was filtered, and the filter cake was washed with methanol and toluene in turn, and dried to obtain deprotonated graphene oxide; it was added into a high-pressure reactor, and 8 parts of propylene oxide were added under nitrogen conditions, and reacted at 90°C for 1 h. After the reaction, distilled water was added to terminate the reaction. After filtering, the filter cake was washed with ethanol and water in turn and dried to obtain linear polyether modified graphene oxide.

[0025] Dendritic polyether modified graphene oxide 1 S1. Add 1 part of 1,7-bis-BOC-1,4,7-triazaheptane and 30 parts of anhydrous dimethyl sulfoxide solution to a reaction kettle. Under a nitrogen atmosphere, add potassium iodide and heat to 110 °C. Then slowly add 1.05 parts of 3-chloropropyltriethoxysilane. After reacting for 12 h, cool to room temperature, remove the solvent by rotary evaporation, wash with anhydrous ether, and vacuum dry to obtain a modified silane coupling agent. S2. Ultrasonic dispersion of 1 part of graphene oxide in 100 parts of anhydrous ethanol for 30 min, then adjusting the pH to 3-4 with 4 mol / L hydrochloric acid solution, transferring it into a reactor, dispersing 3 parts of the modified silane coupling agent obtained in S1 in 10-20 parts of anhydrous ethanol and adding it dropwise in a 60°C water bath, reacting for 5 h, adding 40 parts of trifluoroacetic acid and stirring for 40 min, filtering the obtained solution after the reaction, washing the filter cake with anhydrous ethanol and deionized water in turn, and drying to obtain amino-modified graphene oxide; S3. Add 1 part of amino-modified graphene oxide and 70 parts of dry tetrahydrofuran into a beaker and ultrasonicate for 30 min. Transfer it to a reactor under a nitrogen atmosphere at a temperature of 0-5 °C, add 3 parts of propylene oxide, heat to room temperature for 2 h, then heat to 50-60 °C for 10 h. After the reaction is completed, filter the obtained solution, wash the filter cake with anhydrous ethanol, and dry to obtain polyhydroxy-modified graphene oxide. S4. Add 1 part of the polyhydroxy-modified graphene oxide obtained in S3 into a reactor, add 6 parts of sodium methoxide solution and 60 parts of methanol solution under nitrogen conditions, and stir at 70°C for 3 h. Filter the obtained solution, wash the filter cake with methanol and toluene in turn, and dry to obtain deprotonated polyhydroxy-modified graphene oxide; add it into a high-pressure reactor, add 20 parts of propylene oxide under nitrogen conditions, and react at 90°C for 1 h. After the reaction, add distilled water to terminate the reaction. After filtering, wash the filter cake with ethanol and water in turn and dry to obtain branch polyether modified graphene oxide.

[0026] Dendritic polyether modified graphene oxide 2 Compared with the preparation direction of the dendritic polyether modified graphene oxide 1, the difference is that the reaction at 90°C for 1 h in step S4 is replaced by the reaction at 90°C for 2 h.

[0027] Dendritic polyether modified graphene oxide 3 Compared with the preparation direction of the dendritic polyether modified graphene oxide 1, the difference is that the reaction at 90°C for 1 h in step S4 is replaced by the reaction at 90°C for 3 h.

[0028] The following is the test method of the performance parameters involved in the present invention: (1) Crystalline interplanar spacing: The crystal phases of graphene oxide and modified graphene oxide samples were analyzed and identified using a German Bruker X-ray diffractometer. The X-ray radiation source used for characterization was Cu Kα, the monochromator was graphite, the test current was 40 mA, the test voltage was 40 KV, the diffraction angle range 2θ was 5~35, and the scanning speed was 5 o / min; Interplanar spacing by: Bragg formula , calculate, where: d: is the interplanar spacing, θ is the diffraction half angle, The wavelength of the CuKα target used is 1.54 Å; (2) Dispersion characterization: The dispersion of graphene oxide and modified graphene oxide samples with a mass fraction of 0.5% was diluted 100 times with deionized water, and the absorbance of the sample at a wavelength of 226 nm was tested and observed for 30 days; (3) NMR spectrum: 400 MHz NMR spectrometer (Bruker, Germany); (4) Compressive strength: The specimen size is 150 mm × 150 mm × 150 mm and is tested in accordance with the relevant provisions of GB / T 50081-2019; (5) Splitting tensile strength: The specimen size is 150 mm × 150 mm × 150 mm and is tested in accordance with the relevant provisions of GB / T 50081-2019; (6) Anti-seepage performance: The anti-seepage performance of concrete specimens was tested using the water seepage height method in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete"; (7) Mercury injection test: Mercury injection test samples are prepared as pure paste specimens according to the water-cement ratio in the concrete mix. After stirring, the specimens are placed in a cubic grid with a side length of 1 cm. The curing method is the same as that of concrete. When the sample reaches the specified age, it is taken out, dried, and tested using a mercury injection instrument.

[0029] (8) Crack width detection: After the concrete flat plate specimen is formed, the cracks are observed and recorded within 24 hours. The HC-U8 series multifunctional concrete ultrasonic detector produced by Haichuang Hi-Tech Co., Ltd. is used. The crack length is measured by combining cotton thread and steel ruler to ensure the accuracy of each crack length, and is graded according to the "Concrete Structure Design Code".

[0030] Table 1 Characterization of the dispersion of modified graphene oxide

[0031] From Table 1 and Figure 3 The data show that graphite oxide is 10.22 o There is a diffraction peak with an interlayer spacing of 0.865 nm at 7.73 nm for linear polyether modified graphene oxide. o There is a diffraction peak with an interlayer spacing of 1.15 nm at the junction of the graphene oxide and the new diffraction peak shifts to the left, the peak becomes wider, and the intensity weakens, resulting in a decrease in the crystallinity of graphene oxide. This proves that linear polyethers can successfully modify graphene oxide. oThere is a diffraction peak with an interlayer spacing of 1.36 nm, and the new diffraction peak is further shifted to the left. Based on the data of dendritic polyether modified graphene oxide 1~3, it is speculated that the interplanar spacing is positively correlated with the molecular weight of the modifiable groups on the surface of graphene oxide within a certain range. The dispersibility was tested by ultraviolet absorbance, and it was found that its dispersibility was positively correlated with the interplanar spacing.

[0032] Table 2 Formula of anti-cracking admixtures in preparation examples 1 to 10 (kg)

[0033] Steel slag powder and carbide slag need to be ground, screened through a 400-mesh sieve, mixed evenly, and calcined at 600°C for 2 hours before use.

[0034] A method for preparing mass concrete comprises the following steps: 1) Disperse the anti-cracking admixture in water, ultrasonicate for 10 minutes, mix cement, mineral powder, fly ash, sand and gravel according to the mix ratio, stir for 3 minutes, add water and the dispersed anti-cracking admixture, stir for 3 minutes, add the water reducer, continue stirring for 16 minutes, and discharge; 2) Casting, standard curing, demoulding, and obtaining large volume concrete.

[0035] Table 3 Mass concrete formula of Examples 1 to 10 and Comparative Examples 1 to 4 (kg / m 3 )

[0036] Table 4 Performance test of Examples 1 to 6 and Comparative Examples 1 to 4

[0037] It can be seen from the data in Tables 3 and 4 that the addition of the anti-cracking admixture prepared by the present invention can effectively improve the performance of concrete, and its excellent waterproof performance preliminarily proves that the compactness inside the concrete is good.

[0038] Table 5 Porosity test results of Examples 1 to 6 and Comparative Examples 1 to 4

[0039] It can be seen from the data in Table 5 that the addition of the anti-cracking admixture prepared by the present invention can reduce the proportion of harmful pores and multiple harmful pores in concrete, and the concrete has a dense microstructure network inside, which reduces the stress generated by the internal structure of the concrete due to shrinkage or expansion, thereby enhancing the anti-cracking performance of the concrete.

[0040] Table 6 Crack resistance grades of Examples 1 to 6 and Comparative Examples 1 to 4

[0041] It can be seen from the data in Table 6 that the anti-cracking grade of the anti-cracking admixture prepared by the present invention is at level one.

[0042] The applicant declares that the preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all details in detail, nor do they limit the invention to only the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can well understand and use the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An anti-cracking admixture for mass concrete, characterized in that: The anti-cracking admixture comprises, by mass, 50-80 parts of steel slag powder, 20-30 parts of carbide slag, 25-30 parts of anti-cracking agent, and 0.5-1 part of modified graphene oxide; the modified graphene oxide is at least one of linear polyether modified graphene oxide and dendritic polyether modified graphene oxide; the steel slag powder and carbide slag need to be ground, screened, mixed evenly, and calcined at 600-800°C for 1-2 hours before use; The linear polyether-modified graphene oxide is obtained by anionic ring-opening polymerization of deprotonated graphene oxide as an initiator and an epoxy compound; The preparation method of the dendritic polyether modified graphene oxide is: (1) The modified silane coupling agent is used to couple the hydroxyl groups on the surface of graphene oxide, and the protective groups are hydrolyzed to obtain amino-modified graphene oxide; (2) Aminated amino groups and epoxy groups in graphene oxide are ring-opened under alkaline conditions to obtain polyhydroxy-modified graphene oxide; (3) Deprotonating the polyhydroxy-modified graphene oxide and using it as an initiator to undergo anionic ring-opening polymerization with an epoxy compound to obtain dendritic polyether-modified graphene oxide; The modified silane coupling agent has the following molecular structure: , wherein R is at least one of a methyl group and an ethyl group.

2. The anti-cracking admixture for mass concrete according to claim 1, characterized in that: The steel slag powder and carbide slag need to be screened through a 300-400 mesh sieve after being ground.

3. The anti-cracking admixture for mass concrete according to claim 1, characterized in that: The preparation method of the linear polyether modified graphene oxide is as follows: 1 part of graphene oxide and 50-60 parts of methanol solution were ultrasonically treated for 20-30 min and then added to a reactor. 5-6 parts of sodium methoxide solution were added under nitrogen and stirred at 60-70 °C for 3-4 h. The obtained solution was filtered and the filter cake was washed with methanol and toluene in turn, and dried to obtain deprotonated graphene oxide. Add it into a high-pressure reactor, and add 8 to 10 parts of epoxy compound under nitrogen conditions, and react at 80 to 100 ° C for 1 to 3 hours. After the reaction is completed, distilled water is added to terminate the reaction. After filtering, the filter cake is washed with ethanol and water in turn and dried to obtain linear polyether modified graphene oxide.

4. The anti-cracking admixture for mass concrete according to claim 1, characterized in that: The preparation method of the dendritic polyether modified graphene oxide is as follows: S1. Add 1 part of 1,7-bis-BOC-1,4,7-triazaheptane and 20-30 parts of anhydrous dimethyl sulfoxide solution to a reaction kettle. Under a nitrogen atmosphere, add potassium iodide and heat to 100-110 °C. Then slowly add 1.05-1.1 parts of 3-chloropropyltriethoxysilane. After reacting for 10-12 hours, cool to room temperature, remove the solvent by rotary evaporation, wash with anhydrous ether, and vacuum dry to obtain a modified silane coupling agent. S2. Ultrasonic dispersion of 1 part of graphene oxide in 100-120 parts of anhydrous ethanol for 30-40 min, then adjusting the pH to 3-4 with 3-4 mol / L hydrochloric acid solution, transferring it into a reactor, dispersing 2-3 parts of the modified silane coupling agent obtained in step S1 in 10-20 parts of anhydrous ethanol and adding dropwise thereto in a water bath at 60-70 °C, reacting for 5-6 h, adding 30-40 parts of trifluoroacetic acid and continuing stirring for 30-40 min, filtering the obtained solution after the reaction, washing the filter cake with anhydrous ethanol and deionized water in turn, and drying to obtain amino-modified graphene oxide; S3. Add 1 part of amino-modified graphene oxide and 70-80 parts of dry tetrahydrofuran into a beaker and ultrasonicate for 30-40 min. Transfer it to a reactor under a nitrogen atmosphere at a temperature of 0-10 °C, add 2-3 parts of propylene oxide, heat to room temperature for reaction for 1-2 h, then heat to 50-60 °C for reaction for 10-16 h. After the reaction, filter the obtained solution, wash the filter cake with anhydrous ethanol, and dry to obtain polyhydroxy-modified graphene oxide. S4. After ultrasonic treatment for 20-30 min, add 1 part of the polyhydroxy-modified graphene oxide obtained in step S3 and 50-60 parts of methanol solution into a reactor, add 5-6 parts of sodium methoxide solution under nitrogen, and stir at 60-70°C for 3-4 h. Filter the obtained solution, wash the filter cake with methanol and toluene in turn, and dry to obtain deprotonated polyhydroxy-modified graphene oxide; add it into a high-pressure reactor, add 20-25 parts of epoxy compound under nitrogen, and react at 80-100°C for 1-3 h. After the reaction, add distilled water to terminate the reaction. After filtering, wash the filter cake with ethanol and water in turn and dry to obtain branch polyether modified graphene oxide.

5. The anti-cracking admixture for mass concrete according to claim 3 or 4, characterized in that: The epoxy compound is one or more of ethylene oxide, propylene oxide and glycidol.

6. A mass concrete, characterized in that: In terms of mix ratio, including cement 320~340 kg / m 3 、Mineral powder 90~100kg / m 3 、Fly ash 50~80 kg / m 3 , sand 800~850 kg / m 3 , Crushed stone 780~820 kg / m 3 , Anti-cracking admixture 95.5~141kg / m 3 , water reducing agent 5~8 kg / m 3 , water 150~180 kg / m 3 ; The anti-cracking admixture is the anti-cracking admixture described in any one of claims 1 to 4.

7. A method for preparing mass concrete according to claim 6, characterized in that: The following steps are involved: 1) Disperse the anti-cracking admixture in water, ultrasonicate for 5-10 minutes, mix cement, mineral powder, fly ash, sand and gravel according to the mix ratio, stir for 2-3 minutes, add water and the dispersed anti-cracking admixture, stir for 2-3 minutes, then add the water reducer, continue stirring for 8-16 minutes, and discharge; 2) Casting, standard curing, demoulding, and obtaining large volume concrete.

Citation Information

Patent Citations

  • Nano mass concrete anti-cracking agent and preparation method thereof

    CN110981264A

  • Modified graphene oxide, preparation method thereof, anticorrosive coating containing modified graphene oxide and preparation method of anticorrosive coating

    CN111978771A

  • Modified graphene modified cement-based composite material and preparation method thereof

    CN112521091A

  • Anti-crack concrete and preparation method thereof

    CN118619627A

  • Graphene oxide reinforced cement and concrete

    WO2013096990A1